Almond snacking modestly improves diet quality and waist circumference but not psychosocial assessments and other cardiometabolic markers in overweight, middle-aged adults: A randomized, crossover trial - Vernon Uganiza Rayo; Lauren Okamoto; Maricarmen Cervantes; Mee Young Hong; Nathaniel Jason; Mark Kern; Changqi Liu; Elise North; Svitlana Storm; Oliver C. Witard; Shirin Hooshmand (Human Nutrition & Metabolism)
Almonds are a plant-based source of lipids, proteins, fibers, micronutrients, and phytochemicals associated with cardiometabolic health benefits. We examined blood glucose homeostasis, lipid profile, anthropometrics, blood pressure, food cravings, and mood both pre- and post-feeding, using a randomized, crossover design with 26 healthy adults (37±6 y) consuming either ALMOND (57 g/d) or an isocaloric amount of pretzels (CONTROL) for 8 weeks. Almond supplementation was expected to improve all primary outcomes when compared to CONTROL. ALMOND improved diet quality through increased intakes of monounsaturated fat (Δ+58 %), polyunsaturated fat (Δ+24 %), α-tocopherol (Δ+133 %), β-tocopherol (Δ+33 %), and magnesium (Δ+30 %) relative to CONTROL (Interaction: all p < 0.05). Copper intake increased (Δ+27 %) and sodium decreased (Δ-20 %) during ALMOND (Time: all p < 0.05). A reduction in waist circumference (Δ-1.1 cm) and decrease in carbohydrate intake (Δ-20 %) was observed during ALMOND vs. CONTROL (Trial: all p < 0.05). Insulin sensitivity decreased during CONTROL (Time: p < 0.05) but remained constant during ALMOND. Frequency of food cravings over the last 7 days of experimentation increased during ALMOND vs. CONTROL (Interaction: all p < 0.05). No differences in blood lipid profile, physical activity, and assessments of mood were observed between trials (all p > 0.05). This study demonstrates that a 57 g/d serving of almonds modestly improves diet quality and waist circumference. However, almond supplementation elicited no clinically significant benefits on lipid profile, blood pressure, physical activity, and assessments of cravings and mood. Future mechanistic studies are warranted to understand the effect of almond supplementation on cardiometabolic health in various populations. ClinicalTrials.gov Identifier: NCT04787718.